The evolution of standards and data management practices in systems biology - Natalie J Stanford; Katherine Wolstencroft; Martin Golebiewski; Renate Kania; Nick Juty; Christopher Tomlinson; Stuart Owen; Sarah Butcher; Henning Hermjakob; Nicolas Le Novère; Wolfgang Mueller; Jacky Snoep; et al. (Molecular Systems Biology)
Graphical Abstract A recent community survey conducted by Infrastructure for Systems Biology Europe (ISBE) informs requirements for developing an efficient infrastructure for systems biology standards, data and model management.